The Role of English Proficiency in Uzbekistan’s Digital Transformation: Opportunities and Challenges in Education and Business (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Uzbekistan’s rapid digital transformation is reshaping education, IT, healthcare, business and governance. English proficiency plays a crucial role because English as a global language opens up opportunities for accessing knowledge, experience, and technology worldwide. However, this reliance on English can be problematic. This paper will analyze how English proficiency influences Uzbekistan’s digital transformation, particularly in education, healthcare, business, and technological developments. It also aims to explore the challenges (language barriers) and benefits of using English (global connectivity, economic growth) in digital transformation.